Pembentukan Karakter Islami pada Siswa di SMP Swasta Se-Kota Binjai - Muhandis Alfalah; Yusnaili Budianti; Azizah Hanum OK (Jayapangus Press, 2023)
The purpose of this study was to analyze the methods, the inhibiting factors in the process of forming students' Islamic character and the solutions used as a reference in the formation of students' Islamic character in private junior high schools in Binjai City. The method of this research s to use qualitative research methods in order to reveal in depth data and facts about the formation of the Islamic character of students in private junior high schools throughout the City of Binjai. Data collection techniques using interviews, observation, and document review. Then the data were analyzed by data reduction, data presentation, and conclusion. The results of this study are that the formation of the Islamic character of students s taken from two schools, inamely Al Kaffah Binjai integrated Islamic Middle School and Binjai PABA Middle School, each school has a method of forming students' Islamic character. However, in essence the methods used by each school are closely related to the formation of the Islamic character of students. The methods used are giving advice, getting used to good morals, exemplary, Targhib and Tarhib, stories, and parables. in carrying out these methods, inhibiting factors were also found in the formation of Islamic character of students. inhibiting factors that occur due to the lack of religious education in the family, unfavorable environment, lack of awareness of students to carry out conditions related to religion and rampant information from social media. The solution to these inhibiting factors s to prepare professional educators, create a good environment, complete infrastructure, and create intra-curricular and extra-curricular programs as supports in the formation of Islamic character of students at Al Kaffah Binjai integrated Islamic Middle School and Binjai PABA Middle School.